Characteristics and Predictors of Postural Control Impairment in Patients With COPD Participating in a Pulmonary Rehabilitation Program. Issue 3 (26th May 2023) - Pichon, Romain; Ménard, Mathieu; Haering, Diane; Crétual, Armel; Beaumont, Marc
Abstract : Patients with chronic obstructive pulmonary disease (COPD) with impaired postural control had a poorer QoL, lower Pao 2, and higher anxiety scores compared with patients with normal postural control. Predictors of impaired postural control in patients with COPD were symptom-related QoL, Pao 2, inspiratory muscle strength, and body mass index. Abstract : Purpose: Postural control impairment has been identified as a potential extrarespiratory manifestation in patients with chronic obstructive pulmonary disease (COPD). The aims of this study were to identify clinical factors that characterize patients with reduced postural control, to examine the correlation between clinical factors and postural control and to determine predictors of an impaired postural control among COPD participants enrolled in a pulmonary rehabilitation (PR) program. Methods: This study is a secondary analysis of an observational study (PARACHUTE). The baseline assessment of the PR program was used for the analysis. Postural control impairment was defined using the Brief BESTest score (BBT). Results: Participants (n = 73) were included in the analysis, 43 of them were classified in the reduced postural control group. The between-group comparison (non-reduced vs reduced postural control) identified differences for partial pressure in oxygen (PaO 2 ), Saint George Respiratory Questionnaire (SGRQ) total score and subscores (SGRQ-Symptoms, SGRQ-Activities, and SGRQ-Impact), COPD assessment test (CAT), and anxiety score of the Hospital Anxiety and Depression Scale. The BBT score was significantly correlated with maximal inspiratory pressure (MIP), SGRQ, SGRQ-Symptoms, SGRQ-Impact, Falls Efficacy Scale, modified Medical Research Council Scale, 6-min walk test, and PaO 2 . Logistic regression identified SGRQ-Symptoms, PaO 2, MIP, and body mass index (BMI) as predictors of the presence of reduced postural control. Conclusion: Low quality of life (QoL) and PaO 2 and high anxiety seem to be discriminative characteristics of patients with COPD with reduced postural control. Furthermore, QoL, PaO 2, inspiratory muscle strength, and BMI seem to be acceptable predictors of the presence of postural control impairment.